A critical analysis of Islamic equity funds. Issue 1 (13th April 2015) - Clarke, Kai Aaron
Abstract : Purpose: – The purpose of this paper is to highlight the inconsistencies between the methodologies of Islamic funds and indices. Design/methodology/approach: – The paper has reviewed the methodologies of the most prominent funds and indices (5) to apply their apparent screening features to the asset universe. In the analysis conducted, qualitative and quantitative screens are derived from each selected fund and index methodological approach to asset selection subject to Shari'ah constraints. Qualitative screens are applied first followed by quantitative screens. Findings: – Few inconsistencies are evident between the chosen funds and indices when the qualitative screens are applied. However, the major inconsistencies are highlighted after analysis of the quantitative screens. Research limitations/implications: – A number of companies within the asset universe are investment trusts, and such financial statement line item data were not found. However, this posed no difficulty, as these companies were investment trusts and would have been excluded in the qualitative screening process. Social implications: – This paper will assist in the construction of a framework which thus leads to the development of a standardized methodological approach, ultimately benefiting investors. Originality/value: – This paper is believed to be the first which analyzes the impact of Shari'ah screens on the Financial Times Stock Exchange (FTSE). Additionally, this paper also analyzes the impact of Shari'ah screens pre and post the financial crisis. The findings of this research paper will also aid in the construction of a different research methodological approach capable of selecting halal securities listed in the FTSE 250.